2006
DOI: 10.5688/aj7005104
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Affect Academic Performance Among Pharmacy Students

Abstract: Objective. The objective of this study was to examine factors such as academic competence, test competence, time management, strategic studying, and test anxiety, and identify whether these factors could distinguish differences among students, based on academic performance and enrollment in the experiential program. Methods. A cross-sectional study design utilizing questionnaires measuring previously validated constructs was used to evaluate the effect of these factors on students with low and high cumulative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
105
3
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(118 citation statements)
references
References 16 publications
9
105
3
1
Order By: Relevance
“…8,9,12 These studies revealed similar findings with Sansgiry and colleagues' study. 2 However, the latter was conducted at only two US schools of pharmacy and suggested that differences in demographic variables at schools in other locations needed further study.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…8,9,12 These studies revealed similar findings with Sansgiry and colleagues' study. 2 However, the latter was conducted at only two US schools of pharmacy and suggested that differences in demographic variables at schools in other locations needed further study.…”
Section: Introductionsupporting
confidence: 82%
“…13,14 The Test Anxiety Inventory was employed among pharmacy students in the United States, and survey results showed good internal consistency with the instrument items. 8 The 20-item Study Management and Academic Results Test (SMART) measures academic self-efficacy and contains scales for 4 constructs: academic competence, test competence, time management, and strategic studying. The tool was developed and validated by Topman and colleagues in 1994 and the reliability coefficients of its scales ranged from 0.67 to 0.81.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Counseling started at an appropriate stage integrated with medical curriculum and extracurricular activities like yoga, meditation etc is found to have a significant impact on their stress level 32,33,34 . In our study, there was 63% of students reported stress due to academic factors which is well in agreement with the earlier studies due to lack of strategic studying, studying all night before exams, inefficient studying which include lack of review and revising of course material studied are major factors leading to exam related anxiety 35 . 59% of students have reported exam related anxiety due to skipping of food and improper nutrition during exams is well in accordance with earlier reports 36 .…”
Section: Discussionsupporting
confidence: 80%